Clinical Outcomes, Echocardiographic Findings, and Care Quality Metrics for People Living With Human Immunodeficiency Virus (HIV) and Rheumatic Heart Disease in Uganda. (12th August 2021) - Chang, Andrew Y; Rwebembera, Joselyn; Bendavid, Eran; Okello, Emmy; Barry, Michele; Beaton, Andrea Z; Haeffele, Christiane; Webel, Allison R; Kityo, Cissy; Longenecker, Chris T
Abstract: Background: Rheumatic heart disease (RHD) affects 41 million people worldwide, mostly in low- and middle-income countries, where it is co-endemic with human immunodeficiency virus (HIV). HIV is also a chronic inflammatory disorder associated with cardiovascular complications, yet the epidemiology of patients affected by both diseases is poorly understood. Methods: Utilizing the Uganda National RHD Registry, we described the echocardiographic findings, clinical characteristics, medication prescription rates, and outcomes of all 73 people carrying concurrent diagnoses of HIV and RHD between 2009 and 2018. These individuals were compared to an age- and sex-matched cohort of 365 subjects with RHD only. Results: The median age of the HIV-RHD group was 36 years (interquartile range [IQR] 15), and 86% were women. The HIV-RHD cohort had higher rates of prior stroke/transient ischemic attack (12% vs 5%, P = .02) than the RHD-only group, with this association persisting following multivariable adjustment (odds ratio [OR] 3.08, P = .03). Prevalence of other comorbidities, echocardiographic findings, prophylactic penicillin prescription rates, retention in clinical care, and mortality were similar between the 2 groups. Conclusions: Patients living with RHD and HIV in Uganda are a relatively young, predominantly female group. Although RHD-HIV comorbid individuals have higher rates of stroke, their similar all-cause mortality and RHD care quality metrics (such as retention in care) compared to those with RHD alone suggest rheumatic heart disease defines their clinical outcome more than HIV does. We believe this study to be one of the first reports of the epidemiologic profile and longitudinal outcomes of patients who carry diagnoses of both conditions. Abstract : Rheumatic heart disease (RHD) and human immunodeficiency virus (HIV) are highly endemic in low-income countries, but comorbidity is poorly understood. This study is the first longitudinal epidemiologic description of outcomes and quality of care for those living with RHD and HIV in Uganda.